Intracorporeal modified delta-shaped gastroduodenostomy during 2-port distal gastrectomy: technical aspects and short-term outcomes - Lee, Sejin; Song, Jeong Ho; Park, Sung Hyun; Cho, Minah; Kim, Yoo Min; Hyung, Woo Jin; Kim, Hyoung-Il (Annals of surgical treatment and research, 2023)
Surgeons have become increasingly interested in reduced-port gastrectomy to minimize trauma while maintaining oncologic safety. Although gastroduodenostomy has the benefits of better nutritional outcomes and fewer postoperative complications than other types of reconstruction, gastroduodenostomy is not a preferred option for reduced-port distal gastrectomy because of technical difficulties. In this study, we describe our intracorporeal modified delta-shaped gastroduodenostomy technique, which is easily applicable during 2-port distal gastrectomy.PurposeSurgeons have become increasingly interested in reduced-port gastrectomy to minimize trauma while maintaining oncologic safety. Although gastroduodenostomy has the benefits of better nutritional outcomes and fewer postoperative complications than other types of reconstruction, gastroduodenostomy is not a preferred option for reduced-port distal gastrectomy because of technical difficulties. In this study, we describe our intracorporeal modified delta-shaped gastroduodenostomy technique, which is easily applicable during 2-port distal gastrectomy.We retrospectively reviewed our database of 30 consecutive patients with gastric cancer who underwent 2-port distal gastrectomy with intracorporeal modified delta-shaped gastroduodenostomy from October 2016 to May 2021. In this reduced-port approach, we used a Tropian Single port (TROPIAN TECH) via a 25-mm transumbilical incision and a 12-mm port at the right flank. All anastomoses were performed using a 60-mm endolinear stapler. We used 3 additional sutures to provide proper traction and support for the anastomosis.MethodsWe retrospectively reviewed our database of 30 consecutive patients with gastric cancer who underwent 2-port distal gastrectomy with intracorporeal modified delta-shaped gastroduodenostomy from October 2016 to May 2021. In this reduced-port approach, we used a Tropian Single port (TROPIAN TECH) via a 25-mm transumbilical incision and a 12-mm port at the right flank. All anastomoses were performed using a 60-mm endolinear stapler. We used 3 additional sutures to provide proper traction and support for the anastomosis.Mean ± standard deviation of operation time was 148.9 ± 34.7 minutes; reconstruction time was 13.2 ± 4.6 minutes; estimated blood loss was 29.3 ± 44.4 mL; and length of hospital stay was 4.5 ± 1.2 postoperative days. A total of 11 patients (36.7%) had a Clavien-Dindo grade I or grade II complication, and there were no grade IIIa or higher complications.ResultsMean ± standard deviation of operation time was 148.9 ± 34.7 minutes; reconstruction time was 13.2 ± 4.6 minutes; estimated blood loss was 29.3 ± 44.4 mL; and length of hospital stay was 4.5 ± 1.2 postoperative days. A total of 11 patients (36.7%) had a Clavien-Dindo grade I or grade II complication, and there were no grade IIIa or higher complications.Intracorporeal modified delta-shaped gastroduodenostomy was safely performed via a 2-port approach, resulting in acceptable surgical outcomes and no major complications.ConclusionIntracorporeal modified delta-shaped gastroduodenostomy was safely performed via a 2-port approach, resulting in acceptable surgical outcomes and no major complications.